Perancangan Strategi Bisnis Dengan Analisis Swot dan Business Model Canvas (Bmc) Pada UKM XYZ - Puspitasari, Intan; Nurmaisya Al Ghonia; Nadila Faiza; Alvi Khumairoh; Maulida Lutfia Aminin; Tri Puspita Ningrum; Lindawati Kartika (Trending: Jurnal Manajemen dan Ekonomi, 2024)
The development and progress of Business Trends occurs very quickly. One of them is the change of business to be digital-based, which makes business competition more competitive. To face this competition, companies need to continue to innovate and be more creative in developing their business strategies. This study aims to analyze the external and internal conditions of SMEs XYZ engaged in dairy products. Using a qualitative approach, this study was analyzed through two methods, namely Business Model Canvas (BMC) and SWOT Analysis. The results of this study indicate that XYZ SMEs are in a hold and maintain position with an internal score of 3.48 and an external score of 3.12 meaning that XYZ SMEs need to maintain and strengthen their internal position and continue to monitor and adjust to changes in the external environment to ensure sustainable growth.